Analisis Kualitatif Tampilan Visual Pada Situs E-Learning - Andi Aulia Hamzah; Achmad Syarief; Ifa Safira Mustikadara (Journal of Visual Art and Design, 2013)
This research attempts to identify the influence of visuals of e-learning websites on learning motivation. The investigated object is e-learning sites of ilmukomputer.com and pendidikan.ws, which presents differences of interactivity. Results of investigation on the visual appearance of both websites indicate that level of complexity of an e-learning website affects the presentation of information for learners. The presented visuals assist learners to dwelve into the subjects, visuals directly influence 33.5% of learners' motivation. Therefore, one should emphasize visual preparation of information and instruction design when creating an e-learning website.